Antibacterial molded article

The antibacterial molded product using a polycarbonate resin with a specific structural unit and glass transition temperature range addresses the challenges of antibacterial properties, transparency, heat resistance, and moldability, offering a versatile and environmentally friendly solution for diverse applications.

JP2025060597AActive Publication Date: 2025-04-10TEIJIN LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024205922
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-10
Estimated Expiration
2040-09-01

AI Technical Summary

Technical Problem

Existing antibacterial molded products using polycarbonate resins face challenges in achieving excellent antibacterial properties, transparency, heat resistance, and moldability while being cost-effective and safe.

Method used

The development of an antibacterial molded product using a polycarbonate resin with a specific structural unit, characterized by a glass transition temperature between 40°C and 150°C, which enhances antibacterial properties, transparency, heat resistance, and moldability.

Benefits of technology

The antibacterial molded product exhibits exceptional antibacterial properties, transparency, heat resistance, and moldability, making it suitable for various applications, including home equipment and medical devices, while being environmentally friendly and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060597000001
    Figure 2025060597000001
  • Figure 2025060597000002
    Figure 2025060597000002
  • Figure 2025060597000003
    Figure 2025060597000003
Patent Text Reader

Abstract

To provide an antibacterial molded article using a polycarbonate resin excellent in antibacterial properties, transparency, heat resistance and moldability.SOLUTION: The antibacterial molded article is characterized in that at least a part of the surface of a molded article is coated with a polycarbonate resin containing a constituent unit represented by the following formula (1) and having a glass transition temperature of 40°C or higher and 150°C or lower. (In formula (1), R1 and R2 each independently represent a hydrogen atom or a C1-4 aliphatic hydrocarbon; m is 1-4; and n is 2-150.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an antibacterial molded article, and more particularly to an antibacterial molded article using a polycarbonate resin containing a specific structure. [Background technology]

[0002] In recent years, from the viewpoint of hygiene and cleanliness, there is a demand for materials with antibacterial properties for the exteriors of home appliances such as toilets, home appliances such as refrigerators and air conditioners, medical equipment, ATMs (automated teller machines), POS terminals, mobile phones, smartphones, etc. installed in convenience stores. Conventionally, various methods have been used to give materials antibacterial properties. For example, one example is a manufacturing method in which an active antibacterial substance is mixed and kneaded during the manufacturing process. Among these, polycarbonate resin has been widely used in electronic devices, office machines, machinery, automobiles, etc., due to its excellent heat resistance and impact resistance. As a method for imparting antibacterial properties to polycarbonate (PC) resin, a method of adding various phosphorus-based or phenol-based antioxidants, heat stabilizers, acid-modified olefin waxes to inorganic antibacterial agents (for example, calcium phosphate, zeolite, zirconium phosphate, etc. carrying antibacterial metal ions such as silver, copper, and zinc) (see Patent Documents 1 to 3), a method of adding an antibacterial agent containing glass that elutes silver ions (Patent Document 4), a method of adding an inorganic composite containing zinc as an essential component as an antibacterial component, and the like have been proposed. However, these methods use expensive antibacterial agents, so although they show a certain level of antibacterial performance, they are expensive. In addition, in general, many of the antibacterial agents themselves have a certain level of toxicity, which poses safety problems. Furthermore, the inclusion of an antibacterial agent impairs the transparency of the resin itself, and the transparency may be insufficient depending on the application.

[0003] On the other hand, in recent years, due to concerns about the depletion of petroleum resources and the problem of an increase in carbon dioxide in the air that causes global warming, biomass resources that do not rely on petroleum as a raw material and are carbon neutral without increasing carbon dioxide even when burned have attracted a lot of attention, and in the field of polymers, biomass plastics produced from biomass resources have been actively developed. As an amorphous polycarbonate resin that uses biomass resources as a raw material and has high heat resistance, a polycarbonate resin using a raw material obtained from an ether diol residue that can be produced from carbohydrates has been studied. In particular, it has been studied to incorporate isosorbide as a monomer into polycarbonate (Patent Document 6). In a series of studies, it has been reported that polycarbonate containing isosorbide has bacteriorepellency as an inherent characteristic of the resin (Non-Patent Document 1). In the non-patent documents, it has been shown that the higher the isosorbide ratio, the better the bacteriorepellency, and isosorbide homopolymer has the highest bacteriorepellency. However, according to the study by the present inventors, it was found that the antibacterial properties of isosorbide homopolymer are insufficient for use in antibacterial products. In addition, although various PCs made from polyethylene glycol have been reported, they were not aimed at improving the antibacterial properties (Patent Documents 7 and 8). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 6-240125 [Patent Document 2] Japanese Patent Application Publication No. 10-168294 [Patent Document 3] Japanese Patent Application Publication No. 11-323117 [Patent Document 4] JP 2011-137068 A [Patent Document 5] JP 2005-239904 A [Patent Document 6] International Publication No. 2004 / 111106 [Patent Document 7] JP 2011-241277 A [Patent Document 8] Special Publication No. 2002-522584 [Non-patent literature]

[0005] [Non-Patent Document 1] Kobunshi Ronbunshu (Volume 74, No. 6, pages 631-634, 2017) Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an antibacterial molded article using a polycarbonate resin that has excellent antibacterial properties, transparency, heat resistance and moldability. [Means for solving the problem]

[0007] The present inventors have found that a polycarbonate resin containing a specific structure and having a Tg in a specific range is excellent in antibacterial properties, transparency, heat resistance and moldability, and have completed the present invention. According to the present invention, the above-mentioned problems are solved by the following invention.

[0008] 1. An antibacterial molded article, characterized in that at least a portion of the surface of the molded article is coated with a polycarbonate resin containing a structural unit represented by the following formula (1) and having a glass transition temperature of 40°C or higher and 150°C or lower. [ka] (In formula (1), R 1 and R 2 each independently represents a hydrogen atom or an aliphatic hydrocarbon having 1 to 4 carbon atoms; m is 1 to 4, and n is 2 to 150. 2. The antibacterial molded article according to item 1 above, wherein the polycarbonate resin further contains a structural unit represented by the following formula (2): [ka] 3. The antibacterial molded article according to item 1 or 2 above, wherein the polycarbonate resin contains the structural unit represented by formula (1) in an amount of 1% by weight or more and 80% by weight or less, based on 100% by weight of all structural units. 4. The antibacterial molded article according to any one of items 1 to 3 above, wherein the polycarbonate resin has a specific viscosity of 0.15 or more and 1.5 or less. 5. The antibacterial molded article according to any one of the above items 1 to 4, which has a water contact angle of 60° or less. 6. The antibacterial molded article according to any one of items 1 to 5 above, wherein the constitutional unit represented by formula (1) is a constitutional unit represented by the following formula (3): [ka] (In formula (3), R 3 represents a hydrogen atom or a methyl group. n is a number from 2 to 150. 7. The antibacterial molded article according to any one of items 1 to 6 above, which is an antibacterial molded article for housing equipment, refrigerators, home appliances, ATMs (automated teller machines), POS terminals, mobile phones, smartphones, PCs, tablets, packaging materials, wallpaper, filters, switches, daily necessities and living materials, sanitary materials, clothing, and vehicles. 8. The antibacterial molded article according to any one of items 1 to 7 above, wherein the components constituting the antibacterial molded article have a shape of a porous body, fiber, nonwoven fabric, particle, film, sheet, tube or powder. 9. The antibacterial molded article according to any one of the preceding items 1 to 8, wherein the coating has a thickness of 0.1 μm to 1 mm. 10. The antibacterial molded article according to any one of the above items 1 to 9, wherein the polycarbonate resin is coated by a painting method, a spraying method or a dipping method. Effect of the Invention

[0009] The antibacterial molded products using the polycarbonate resin used in the present invention have excellent antibacterial properties, transparency, heat resistance and moldability, and can therefore be used in a wide variety of applications, including home appliances such as toilets, home appliances such as refrigerators and air conditioners, medical equipment, ATMs (automated teller machines) installed in convenience stores, POS terminals, mobile phones, smartphones, PCs, tablets, various packaging materials, wallpaper, various filters, various switches, daily necessities and living materials, sanitary materials, clothing, and various plastic parts related to vehicles, and the industrial effects they bring are exceptional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, each component of the polycarbonate resin used in the present invention, the blending ratio thereof, the preparation method, etc. will be described in detail in order.

[0011] <Polycarbonate resin> The polycarbonate resin used in the present invention contains a structural unit represented by the following formula (1).

[0012] [ka]

[0013] In formula (1), m is 1 to 4, n is 2 to 150, and R 1 and R 2 each independently represents a hydrogen atom or an aliphatic hydrocarbon having 1 to 4 carbon atoms. Among them, m is preferably 2 to 4, and particularly preferably 2. The degree of polymerization n is preferably 2 to 100, more preferably 2 to 50, and particularly preferably 2 to 35.

[0014] The repeating unit in formula (1) is usually derived from a polyoxyalkylene glycol. The number average molecular weight of the polyoxyalkylene glycol used is preferably 100 to 20,000, more preferably 100 to 5,000, and particularly preferably 200 to 2,000. Within this range, the balance of flexibility, heat resistance, and antibacterial properties is excellent, and if it is outside this range, transparency may not be obtained or the product may become water-soluble and cannot be used as a molded product.

[0015] More specific examples of polyoxyalkylene glycols include polyethylene glycol, polytrimethylene glycol, polytetramethylene glycol, and polypropylene glycol.

[0016] In particular, polyoxyalkylene glycols represented by the following formula (3), that is, polyethylene glycol or polypropylene glycol, are preferably used.

[0017] [ka]

[0018] In formula (3), n is 2 to 150, and R 3 represents a hydrogen atom or a methyl group. The content of the structural unit represented by formula (1) or (3) is preferably 1% by weight or more, more preferably 5% by weight or more, even more preferably 10% by weight or more, and particularly preferably 15% by weight or more, based on 100% by weight of all structural units. The upper limit of the content is preferably 80% by weight or less, more preferably 70% by weight or less, even more preferably 50% by weight or less, and particularly preferably 30% by weight or less. By setting the weight ratio in this way, the balance between antibacterial properties, heat resistance, and moldability is excellent, which is preferable. The weight ratio can be measured and calculated by proton NMR using JNM-AL400 manufactured by JEOL Ltd.

[0019] The polycarbonate resin used in the present invention preferably further contains a structural unit represented by formula (2).

[0020] [ka]

[0021] The above formula (2) is exemplified by structural units (2-1), (2-2) and (2-3) represented by the following formulae, which are stereoisomeric.

[0022] [ka]

[0023] [ka]

[0024] [ka]

[0025] These are ether diols derived from carbohydrates, and are also obtained from biomass in nature, making them one of the renewable resources. The building blocks (2-1), (2-2) and (2-3) are called isosorbide, isomannide and isoidide, respectively. Isosorbide is obtained by hydrogenating D-glucose obtained from starch, followed by dehydration. Other ether diols can be obtained by the same reaction, except for the starting material.

[0026] Among isosorbide, isomannide and isoidide, the structural unit derived from isosorbide (1,4;3,6-dianhydro-D-sorbitol) is particularly preferred because of ease of production and excellent heat resistance.

[0027] The content ratio of the structural unit represented by the formula (2) is preferably 20% by weight or more, more preferably 30% by weight or more, even more preferably 40% by weight or more, particularly preferably 50% by weight or more, and most preferably 70% by weight or more, based on 100% by weight of all structural units. The upper limit of the content ratio is preferably 99% by weight or less, more preferably 95% by weight or less, even more preferably 92% by weight or less, and particularly preferably 90% by weight or less. By setting the weight ratio in this way, the balance of antibacterial properties, heat resistance, moldability, and biomass degree is excellent, which is preferable. The weight ratio can be measured and calculated by proton NMR using JNM-AL400 manufactured by JEOL Ltd.

[0028] The polycarbonate resin used in the present invention may contain other structural units derived from various diol compounds other than the structural units represented by the formula (1) and the formula (2). The content ratio of the other structural units is preferably 30% by weight or less, more preferably 20% by weight or less, further preferably 10% by weight or less, and particularly preferably 5% by weight or less, based on 100% by weight of all structural units. Such diol compounds (diol monomers) may be any of aliphatic diol compounds, alicyclic diol compounds, and aromatic dihydroxy compounds, and include diol compounds described in WO 2004 / 111106 and WO 2011 / 021720. These may be used alone or in combination of two or more. Representative specific examples of the diol component are shown below, but are not limited thereto.

[0029] Examples of the aliphatic diol compound include 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-n-butyl-2-ethyl-1 ,3-propanediol, 2,2-diethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexane glycol, 1,2-octyl glycol, 2-ethyl-1,3-hexanediol, 2,3-diisobutyl-1,3-propanediol, 2,2-diisoamyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, and the like.

[0030] Examples of the alicyclic diol compound include cyclohexane dimethanol, tricyclodecane dimethanol, adamantane diol, pentacyclopentadecane dimethanol, 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane, 2,2,4,4-tetramethylcyclobutanediol, 1,1'-spirobiindane-6,6'-diol, decalin-2,6-dimethanol, norbornane dimethanol, and cyclopentane-1,3-dimethanol.

[0031] Examples of the aromatic dihydroxy compound include α,α'-bis(4-hydroxyphenyl)-m-diisopropylbenzene (bisphenol M), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, bisphenol A, 2,2-bis(4-hydroxy-3-methylphenyl)propane (bisphenol C), 2,2-bis(4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoro Propane (bisphenol AF), biphenol, 1,1-bis(4-hydroxyphenyl)decane, bis(2-hydroxyethoxy)naphthalene, 9,9-bis(4-(2-hydroxyethoxy)phenyl)-1,8-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-methylphenyl)-1,8-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)-1,8-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-1-naphthyl)-1,8-diphenylfluorene fluorene, 9,9-bis(6-(2-hydroxyethoxy)-2-naphthyl)-1,8-diphenylfluorene, 9,9-bis(4-hydroxyphenyl)-1,8-diphenylfluorene, 9,9-bis(4-hydroxy-3-methylphenyl)-1,8-diphenylfluorene, 9,9-bis(4-hydroxy-3-phenylphenyl)-1,8-diphenylfluorene, 9,9-bis(4-hydroxy-1-naphthyl)-1,8-diphenylfluorene, 9,9-bis(6-hydroxy-2-naphthyl)-1,8-diphenylfluorene, 9,9-bis 9,9-bis(4-(2-hydroxyethoxy)phenyl)-2,7-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-methylphenyl)-2,7-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)-2,7-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-1-naphthyl)-2,7-diphenylfluorene, 9,9-bis(6-(2-hydroxyethoxy)-2-naphthyl)-2,7-diphenylfluorene, 9,9-bis(4-hydroxyphenyl)-2,7-diphenylfluorene, 9,9-bis(4-hydroxy-3-methylphenyl)-2,7-diphenylfluorene, 9,9-bis(4-hydroxy-3-phenylphenyl)-2,7-diphenylfluorene, 9,9-bis(4-hydroxy-1-naphthyl)-2,7-diphenylfluorene, 9,9-bis(6-hydroxy-2-naphthyl)-2,7-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)phenyl)-3,6-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-methylphenyl) -3,6-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)-3,6-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-1-naphthyl)-3,6-diphenylfluorene, 9,9-bis(6-(2-hydroxyethoxy)-2-naphthyl)-3,6-diphenylfluorene, 9,9-bis(4-hydroxyphenyl)-3,6-diphenylfluorene, 9,9-bis(4-hydroxy-3-methylphenyl)-3,6-diphenylfluorene, 9,9-bis(4-hydroxy -3-phenylphenyl)-3,6-diphenylfluorene, 9,9-bis(4-hydroxy-1-naphthyl)-3,6-diphenylfluorene, 9,9-bis(6-hydroxy-2-naphthyl)-3,6-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)phenyl)-4,5-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-methylphenyl)-4,5-diphenylfluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)-4,5-diphenylfluorene, 9, 9-bis(4-(2-hydroxyethoxy)-1-naphthyl)-4,5-diphenylfluorene, 9,9-bis(6-(2-hydroxyethoxy)-2-naphthyl)-4,5-diphenylfluorene, 9,9-bis(4-hydroxyphenyl)-4,5-diphenylfluorene, 9,9-bis(4-hydroxy-3-methylphenyl)-4,5-diphenylfluorene, 9,9-bis(4-hydroxy-3-phenylphenyl)-4,5-diphenylfluorene, 9,9-bis(4-hydroxy-1-naphthyl)-4,5-diphenylfluorene, 9,Examples of the 9-bis(6-hydroxy-2-naphthyl)-4,5-diphenylfluorene include 2,2'-bis(2-hydroxyethoxy)-3,3'-diphenyl-1,1'-binaphthyl, 2,2'-bis(2-hydroxyethoxy)-6,6'-diphenyl-1,1'-binaphthyl, 2,2'-bis(2-hydroxyethoxy)-7,7'-diphenyl-1,1'-binaphthyl, 2,2'-bis(2-hydroxyethoxy)-3,3'-dimethyl-1,1'-binaphthyl, 2,2'-bis(2-hydroxyethoxy)-6,6'-dimethyl-1,1'-binaphthyl, 2,2'-bis(2-hydroxyethoxy)-7,7'-dimethyl-1,1'-binaphthyl, 1,1'-bi-2-naphthol, and dihydroxynaphthalene.

[0032] (Production method of polycarbonate resin) The polycarbonate resin used in the present invention is produced by a reaction means known per se for producing ordinary polycarbonate resins, for example, a method of reacting a diol component with a carbonate precursor such as a carbonic acid diester. Next, the basic means for these production methods will be briefly described.

[0033] The transesterification reaction using a carbonic acid diester as a carbonate precursor is carried out by a method in which a predetermined ratio of diol components is heated and stirred with a carbonic acid diester under an inert gas atmosphere, and the alcohol or phenols produced are distilled off. The reaction temperature varies depending on the boiling point of the alcohol or phenols produced, but is usually in the range of 120 to 300°C. The reaction is completed by reducing the pressure from the beginning of the reaction to distill off the alcohol or phenols produced. In addition, a terminal terminator, an antioxidant, etc. may be added as necessary.

[0034] The carbonic acid diester used in the transesterification reaction includes esters of aryl groups and aralkyl groups having 6 to 12 carbon atoms, which may be substituted. Specific examples include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, and m-cresyl carbonate. Among these, diphenyl carbonate is particularly preferred. The amount of diphenyl carbonate used is preferably 0.97 to 1.10 mol, more preferably 1.00 to 1.06 mol, per mol of the total of the dihydroxy compounds.

[0035] In the melt polymerization method, a polymerization catalyst can be used to increase the polymerization rate. Examples of such a polymerization catalyst include alkali metal compounds, alkaline earth metal compounds, nitrogen-containing compounds, and metal compounds.

[0036] As such compounds, organic acid salts, inorganic salts, oxides, hydroxides, hydrides, alkoxides, quaternary ammonium hydroxides, etc. of alkali metals or alkaline earth metals are preferably used, and these compounds can be used alone or in combination.

[0037] Examples of alkali metal compounds include sodium hydroxide, potassium hydroxide, cesium hydroxide, lithium hydroxide, sodium hydrogen carbonate, sodium carbonate, potassium carbonate, cesium carbonate, lithium carbonate, sodium acetate, potassium acetate, cesium acetate, lithium acetate, sodium stearate, potassium stearate, cesium stearate, lithium stearate, sodium borohydride, sodium benzoate, potassium benzoate, cesium benzoate, lithium benzoate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, dilithium hydrogen phosphate, disodium phenylphosphate, disodium salt, dipotassium salt, dicesium salt, and dilithium salt of bisphenol A, and sodium, potassium, cesium, and lithium salts of phenol.

[0038] Examples of alkaline earth metal compounds include magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, magnesium carbonate, calcium carbonate, strontium carbonate, barium carbonate, magnesium diacetate, calcium diacetate, strontium diacetate, barium diacetate, and barium stearate.

[0039] Examples of the nitrogen-containing compound include quaternary ammonium hydroxides having an alkyl or aryl group, such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and trimethylbenzylammonium hydroxide. Other examples include tertiary amines, such as triethylamine, dimethylbenzylamine, and triphenylamine, and imidazoles, such as 2-methylimidazole, 2-phenylimidazole, and benzimidazole. Other examples include bases or basic salts, such as ammonia, tetramethylammonium borohydride, tetrabutylammonium borohydride, tetrabutylammonium tetraphenylborate, and tetraphenylammonium tetraphenylborate.

[0040] Examples of the metal compound include zinc aluminum compounds, germanium compounds, organotin compounds, antimony compounds, manganese compounds, titanium compounds, zirconium compounds, etc. These compounds may be used alone or in combination of two or more.

[0041] The amount of the polymerization catalyst used is preferably 1×10 -9 ~1×10 -2 equivalent, preferably 1 x 10 -8 ~1×10 -5 equivalent, more preferably 1×10 -7 ~1×10 -3 is selected within the equivalent range.

[0042] A catalyst deactivator can also be added in the later stage of the reaction. Known catalyst deactivators can be effectively used as the catalyst deactivator, and among these, ammonium salts and phosphonium salts of sulfonic acid are preferred. Furthermore, salts of dodecylbenzenesulfonic acid such as tetrabutylphosphonium dodecylbenzenesulfonate and salts of paratoluenesulfonic acid such as tetrabutylammonium paratoluenesulfonate are preferred.

[0043] As the ester of sulfonic acid, methyl benzenesulfonate, ethyl benzenesulfonate, butyl benzenesulfonate, octyl benzenesulfonate, phenyl benzenesulfonate, methyl paratoluenesulfonate, ethyl paratoluenesulfonate, butyl paratoluenesulfonate, octyl paratoluenesulfonate, phenyl paratoluenesulfonate, etc. are preferably used. Among them, tetrabutylphosphonium dodecylbenzenesulfonate is most preferably used.

[0044] When at least one polymerization catalyst selected from alkali metal compounds and / or alkaline earth metal compounds is used, the amount of these catalyst deactivators used is preferably 0.5 to 50 mol, more preferably 0.5 to 10 mol, and even more preferably 0.8 to 5 mol, per mol of the catalyst.

[0045] (Specific viscosity:η SP ) Specific viscosity of polycarbonate resin (η SP ) has a lower limit of preferably 0.15 or more, more preferably 0.2 or more, even more preferably 0.25 or more, and particularly preferably 0.3 or more. Also, the upper limit is preferably 1.5 or less, more preferably 1.0 or less, even more preferably 0.8 or less, particularly preferably 0.6 or less, and most preferably 0.5 or less. When the specific viscosity is in the above range, the strength and molding processability of the molded article are good.

[0046] The specific viscosity in the present invention is determined by dissolving 0.7 g of polycarbonate resin in 100 ml of methylene chloride at 20° C. using an Ostwald viscometer. Specific viscosity (η SP )=(tt 0 ) / t 0 [t 0 is the time it takes for methylene chloride to fall, and t is the time it takes for the sample solution to fall]

[0047] The specific viscosity can be measured, for example, as follows. First, polycarbonate resin is dissolved in methylene chloride of 20 to 30 times its weight, and the soluble portion is collected by celite filtration. The solution is then removed and the mixture is thoroughly dried to obtain a solid soluble in methylene chloride. 0.7 g of the solid is dissolved in 100 ml of methylene chloride, and the specific viscosity at 20°C is determined using an Ostwald viscometer.

[0048] (Glass transition temperature: Tg) The glass transition temperature (Tg) of the polycarbonate resin has an upper limit of 150° C. or less, preferably 140° C. or less, more preferably 130° C. or less, even more preferably 125° C. or less, and particularly preferably 120° C. or less. The lower limit is 40° C. or more, preferably 50° C. or more, more preferably 60° C. or more, even more preferably 65° C. or more, and particularly preferably 70° C. or more. If the Tg is within the above range, the moldability is good, which is preferable, and the antibacterial material is more suitable in an environment in which it is used. The glass transition temperature (Tg) is measured using a 2910 model DSC manufactured by TA Instruments Japan, Inc. at a heating rate of 20°C / min.

[0049] (5% weight loss temperature: Td) The lower limit of the 5% weight loss temperature of the polycarbonate resin is preferably 280°C, more preferably 300°C, even more preferably 330°C, and particularly preferably 350°C. The upper limit of the 5% weight loss temperature is preferably 400°C, more preferably 390°C, and even more preferably 380°C. Therefore, the 5% weight loss temperature (Td) of the polycarbonate resin (component A) is preferably 280 to 400°C. If the 5% weight loss temperature is within the above range, there is almost no decomposition of the resin when molding using the polycarbonate resin composition of the present invention, which is preferable. The 5% weight loss temperature is measured by a TGA (model TGA2950) manufactured by TA Instruments.

[0050] (water contact angle) The water contact angle of the antibacterial molded article of the present invention is preferably 60° or less, more preferably 58° or less, and even more preferably 56° or less. When the water contact angle is 60° or less, the surface is sufficiently hydrophilic, which is favorable for the expression of antibacterial properties.

[0051] (Total light transmittance) The antibacterial molded article of the present invention has a total light transmittance at a thickness of 2 mm of preferably 80% or more, more preferably 85% or more, even more preferably 88% or more, and particularly preferably 90% or more. When the total light transmittance is within the above range, the molded article is particularly useful because it has excellent transparency and therefore excellent visibility inside the molded article. The term "total light transmittance" as used in connection with the present invention denotes a level of transparency and means the ratio of transmitted light to incident light according to method E308 of ASTM-D1003-61.

[0052] (Additives, etc.) The polycarbonate resin used in the present invention may be blended with a polymer other than the polymer of the present invention, a heat stabilizer, a plasticizer, a light stabilizer, a polymerized metal deactivator, a flame retardant, a lubricant, an antistatic agent, a surfactant, an antibacterial agent, an ultraviolet absorber, a mold release agent, and the like, as long as the antibacterial properties are not impaired.

[0053] <Antibacterial molded products> The antibacterial molded article of the present invention can be obtained by coating at least a part of the surface of the molded article with the polycarbonate resin. Here, the "antibacterial molded article" can be suitably used for home appliances such as toilets, home appliances such as refrigerators and air conditioners, ATMs (automated teller machines) installed in convenience stores, POS terminals, mobile phones, smartphones, personal computers, tablets, various packaging materials, wallpaper, various filters, switches, daily necessities and living materials, sanitary materials, clothing, various plastic parts related to vehicles, etc.

[0054] (Antibacterial activity value) The antibacterial properties of the antibacterial molded article of the present invention are preferably 2.0 or more, more preferably 3.0 or more, as measured by the JIS Z2801 standard when a polycarbonate resin made of bisphenol A is used as an antibacterial untreated sample. If the antibacterial activity value is less than 2, it cannot be said that the proliferation of bacteria can be suppressed.

[0055] (shape) In the present invention, the material and shape of the members constituting the antibacterial molded article are not particularly limited, and may be, for example, any of porous bodies, fibers, nonwoven fabrics, particles, films, sheets, tubes, powders, and the like.

[0056] (Molding method) The polycarbonate resin used in the present invention is molded by any method, such as injection molding, compression molding, extrusion molding, solution casting, electrospinning, etc. The polycarbonate resin used in the present invention has excellent moldability, heat resistance, and antibacterial properties, and can be used as various molded articles.

[0057] The polycarbonate resin used in the present invention can also be extruded to produce various profile extrusions, sheets, films, etc. In addition, the inflation method, calendar method, casting method, etc. can be used to produce sheets and films. Furthermore, it can be molded into a heat-shrinkable tube by a specific stretching operation. The polycarbonate resin used in the present invention can also be molded into a molded product by rotational molding, blow molding, etc.

[0058] (Surface treatment) The antibacterial molded article of the present invention may be one in which the polycarbonate resin used in the present invention is coated on at least a part of the surface of the antibacterial molded article. The method for retaining the polycarbonate resin used in the present invention on the surface of the antibacterial molded article includes a coating method, a spray method, a dipping method, etc., and any of them can be applied without any particular limitation. The film thickness is preferably 0.1 μm to 1 mm. EXAMPLES

[0059] The present invention will be further described below with reference to examples. However, the present invention is not limited to these examples. In the examples, parts are parts by weight and % is % by weight. The evaluation was performed according to the following methods.

[0060] (Evaluation of polycarbonate resin) (1) Polymer composition ratio (NMR) The polymer composition ratio (molar ratio) was calculated by proton NMR using JNM-AL400 manufactured by JEOL Ltd. (2) Specific viscosity (η sp ) The pellets were dissolved in methylene chloride to a concentration of approximately 0.7 g / dL, and the viscosity was measured at 20°C using an Ostwald viscometer (instrument name: RIGO AUTO VISCOSIMETER TYPE VMR-0525·PC). sp was calculated from the following formula. η sp =t / t o -1 t: Time in seconds for sample solution to fall to : Time taken for methylene chloride to fall (3) Glass transition temperature (Tg) The measurement was carried out using a TA Instruments DSC (model DSC2910) by heating about 10 mg of the pellet at a temperature increase rate of 20° C. / min. (4)5% weight loss temperature The measurement was carried out using a TA Instruments TGA (model TGA2950) by heating about 10 mg of the pellet at a temperature increase rate of 20° C. / min.

[0061] (Evaluation of molded products) (1) Formability Molded articles that were visually inspected to have a good appearance were rated ◯, and those that suffered from insufficient drying or a poor appearance were rated x. (2) Total light transmittance A 2 mm section of the obtained molded article was measured using a Hitachi U-3310 spectrophotometer. (3) Water contact angle The water contact angle of the surface of the resulting molded article was measured using a DM-501Hi manufactured by Kyowa Interface Science. (4) Antibacterial properties In accordance with JIS Z2801, a 2 mm thick section of the molded product obtained by the method described below was cut out and used to carry out tests under the following conditions. *Bacterial liquid concentration: 1 / 500NB (NB: Nutrient Borth liquid basal medium) *Bacteria liquid dropping amount: 0.4ml *Storage temperature: 35±1℃ *Storage humidity: 90% or more *Storage time: 24±1 hours *Bacteria used: Staphylococcus aureus (NBRC12732), Escherichia coli (NBRC3972) [Antibacterial evaluation criteria] The antibacterial activity value was used as the evaluation standard for antibacterial properties. Antibacterial activity value = Log (viable bacteria count of untreated sample: polycarbonate made of bisphenol A) - Log (viable bacteria count of antibacterial sample) A: Antibacterial activity value = 3.0 or more (significant antibacterial effect compared to untreated sample) B: Antibacterial activity value = 2.0 or more (antibacterial effect compared to untreated sample) C: Antibacterial activity value = less than 2.0 (not considered to have antibacterial effect)

[0062] [Example 1] <Production of polycarbonate resin> Isosorbide (hereinafter abbreviated as ISS) 491.0 parts, polyethylene glycol (molecular weight 1000, hereinafter abbreviated as PEG1000) 140.0 parts, diphenyl carbonate (hereinafter abbreviated as DPC) 757.3 parts, and barium stearate 3.7 × 10 -3 The part was heated to 180°C under a nitrogen atmosphere to melt it. After it was confirmed that it had melted, the EI reaction process was started. After the start of decompression, the pressure was reduced over 40 minutes while adjusting the final degree of vacuum to 8.0 kPa, and after reaching 8.0 kPa, the degree of vacuum was maintained. At the same time as the start of decompression, the temperature was raised at a rate of 30°C / hr until the final resin temperature reached 220°C. After reaching 220°C, the temperature was maintained for 10 minutes until 80% of the theoretical amount of phenol was distilled off at a vacuum degree of 1.0 kPa and a resin temperature of 220°C. After it was confirmed that 80% had distilled off, the PA reaction process (early stage) was started. The temperature was raised at a rate of 0.5°C / min so that the final resin temperature was 230°C. In parallel with the temperature rise, the pressure was reduced over 60 minutes so that the final degree of vacuum was 1 kPa. Subsequently, the PA reaction process (late stage) was started. In the late stage, the temperature was raised at a rate of 1°C / min so that the final resin temperature was 240°C. In parallel with the temperature rise, the pressure was reduced over 20 minutes until the final reduced pressure reached 134 Pa. When the predetermined stirring power value was reached, the reaction was terminated, and the resin was discharged from the bottom of the reaction tank under nitrogen pressure, cooled in a water tank, and cut into pellets using a pelletizer. The obtained resin was used for various evaluations, and the evaluation results are shown in Table 1.

[0063] <Polycarbonate resin molding> The obtained pellets were dried under vacuum at 50°C for 12 hours, and then an injection molding machine (Japan Steel Works, Ltd., JSW J-75EIII) was used to mold a three-stage plate having a width of 50 mm, a length of 90 mm, and thicknesses of 3.0 mm (length 20 mm), 2.0 mm (length 45 mm), and 1.0 mm (length 25 mm) from the gate side, with an arithmetic mean roughness (Ra) of 0.03 μm, at a molding temperature of 200°C, a mold temperature of 40°C for each mold, and a molding cycle of 50 seconds. The evaluation results are shown in Table 2.

[0064] [Example 2] <Production of polycarbonate resin> ISS501.3 parts, PEG1000 70.0 parts, DPC757.3 parts, and barium stearate 3.7 x 10 as a catalyst -3 The same operations and evaluations as in Example 1 were carried out except that the same parts were used. <Polycarbonate resin molding> The same operations and evaluations as in Example 1 were carried out except that the molding temperature was 230°C and the mold temperature was 70°C.

[0065] [Example 3] <Production of polycarbonate resin> ISS 460.3 parts, polyethylene glycol (molecular weight 400, hereinafter abbreviated as PEG400) 140.0 parts, DPC 757.3 parts, and barium stearate 3.7 × 10 as a catalyst. -3 The same operations and evaluations as in Example 1 were carried out except that the same parts were used. <Polycarbonate resin molding> The same operations and evaluations as in Example 1 were carried out except that the molding temperature was 190°C and the mold temperature was 40°C.

[0066] [Example 4] <Production of polycarbonate resin> 363.2 parts of ISS, 152.4 parts of triethylene glycol (hereinafter abbreviated as TEG), 757.3 parts of DPC, and 3.7 x 10 barium stearate as a catalyst. -3 The same operations and evaluations as in Example 1 were carried out except that the same parts were used. <Polycarbonate resin molding> The same operations and evaluations as in Example 1 were carried out except that the molding temperature was 190°C and the mold temperature was 40°C.

[0067] [Comparative Example 1] <Production of polycarbonate resin> ISS 511.5 parts, DPC 757.3 parts, and barium stearate 3.7 x 10 as a catalyst -3 The same operations and evaluations as in Example 1 were carried out except that the same parts were used. <Polycarbonate resin molding> After drying at 100°C for 8 hours, the mixture was molded at a molding temperature of 250°C and each mold temperature of 90°C, and the rest of the operations and evaluations were the same as in Example 1.

[0068] [Comparative Example 2] <Production of polycarbonate resin> 799.0 parts of bisphenol A, 757.3 parts of DPC, and 2.0 x 10 sodium hydroxide as a catalyst -4 The resin was heated to 200°C under a nitrogen atmosphere using a 1.0°C pressure regulator to melt the resin. After it was confirmed that the resin had melted, the EI reaction process was started. After the pressure reduction started, the pressure was reduced over 20 minutes while adjusting the final degree of vacuum to 8.0 kPa, and after reaching 8.0 kPa, the degree of vacuum was maintained. At the same time as the pressure reduction started, the temperature was raised at a rate of 30°C / hr until the final resin temperature reached 240°C. After reaching 240°C, the temperature was maintained at a reduced pressure of 1.0 kPa and a resin temperature of 240°C for 10 minutes until 80% of the theoretical amount of phenol was distilled off. After it was confirmed that 80% had distilled off, the PA reaction process (early stage) was started. The pressure was reduced over 1.0°C / 60 minutes so that the final resin temperature was 280°C. Subsequently, the PA reaction process (late stage) was started. In the late stage, the temperature was raised at a rate of 1°C / min so that the final resin temperature was 300°C. In parallel with the temperature increase, the pressure was reduced over 20 minutes until the final degree of vacuum reached 134 Pa. The reaction was terminated when a predetermined stirring power value was reached, and the mixture was discharged from the bottom of the reaction tank under nitrogen pressure, and while cooling in a water tank, it was cut with a pelletizer to obtain pellets. The same operations and evaluations as in Example 1 were carried out.

[0069] <Polycarbonate resin molding> After drying at 100°C for 8 hours, the mixture was molded at a molding temperature of 280°C and each mold temperature of 90°C, and the rest of the operations and evaluations were the same as in Example 1.

[0070] [Comparative Example 3] <Production of polycarbonate resin> ISS 429.7 parts, PEG 1000 560.0 parts, DPC 757.3 parts, and barium stearate 3.7 x 10 as a catalyst -3 The same operations and evaluations as in Example 1 were carried out except that the same parts were used. <Polycarbonate resin molding> The pellets were dried at 23°C under vacuum for 12 hours, but they were fused together and could not be molded. Furthermore, when the pellets were molded at 180°C without being dried and at 40°C for each mold, silver was generated, resulting in a poor appearance.

[0071] [Comparative Example 4] <Production of polycarbonate resin> ISS 507.4 parts, polyethylene glycol (molecular weight 6000, hereinafter abbreviated as PEG6000) 168.0 parts, DPC 757.3 parts, and barium stearate 3.7 × 10 as a catalyst -3 Except for using parts of 1,000 parts by weight, the same procedure as in Example 1 was carried out. The polymer was cloudy and brittle, and various evaluations were impossible.

[0072] [Comparative Example 5] ISS 470.6 parts, PEG 1000 280.0 parts, DPC 757.3 parts, and barium stearate 3.7 x 10 as a catalyst -3 The same operations and evaluations as in Example 1 were carried out except that the same parts were used. <Polycarbonate resin molding> The pellets were dried at 23°C under vacuum for 12 hours, but they were fused together and could not be molded. When the pellets were molded at 180°C without being dried and at 40°C for each mold, silver was generated and the appearance was poor.

[0073] [Comparative Example 6] 99.5 parts of the bisphenol A polycarbonate resin obtained in Comparative Example 2 and 0.5 parts of KM10D2, a silver-based antibacterial agent manufactured by Sinanen Zeomic Co., Ltd., were mixed at a melting temperature of 270°C using a twin-screw extruder (TEX30α manufactured by The Japan Steel Works, Ltd., shaft diameter = 30 mmφ, L / D = 41) to obtain pellets for evaluation. Various evaluations were performed using the obtained resin, and the evaluation results are shown in Table 1.

[0074] <Polycarbonate resin molding> The obtained pellets were dried at 100°C for 12 hours, and then molded using an injection molding machine (Japan Steel Works, Ltd., JSW J-75EIII) at a molding temperature of 280°C, a mold temperature of 90°C for each mold, and a molding cycle of 50 seconds into a three-stage plate having a width of 50 mm, a length of 90 mm, and thicknesses of 3.0 mm (length 20 mm), 2.0 mm (length 45 mm), and 1.0 mm (length 25 mm) from the gate side, and an arithmetic mean roughness (Ra) of 0.03 μm. The evaluation results are shown in Table 2.

[0075] [Table 1]

[0076] [Table 2]

[0077] As shown in Table 2, it was found that by including a specific structure in the polycarbonate resin and having a Tg within a specific range, both moldability and antibacterial properties can be achieved. On the other hand, an existing polycarbonate resin composition containing an antibacterial agent as in Comparative Example 6 exhibits antibacterial properties, but is inferior in transparency compared to the inherent transmittance of the resin, and does not contain a biomass raw material, resulting in a large environmental load. The antibacterial molded product of the present invention is particularly suitable for applications such as, for example, housing equipment such as toilets, home appliances such as refrigerators and air conditioners, ATMs (automated teller machines) installed in convenience stores, POS terminals, mobile phones, smartphones, personal computers, tablets, various packaging materials, wallpaper, various filters, switches, daily necessities and living materials, sanitary materials, clothing, and various plastic parts related to vehicles. [Industrial Applicability]

[0078] The polycarbonate resin used in the present invention has excellent antibacterial properties, transparency, heat resistance and moldability, and therefore can be used in a wide variety of applications, including home appliances such as toilets, refrigerators, air conditioners and other home appliances, ATMs (automated teller machines) installed in convenience stores, POS terminals, mobile phones, smartphones, PCs, tablets, various packaging materials, wallpaper, various filters, switches, daily necessities and living materials, sanitary materials, clothing, and various plastic parts related to vehicles.

Claims

1. An antibacterial molded article, comprising at least a portion of a surface of the molded article coated with a polycarbonate resin containing a structural unit represented by the following formula (1) and having a glass transition temperature of 40° C. or higher and 150° C. or lower: 【Chemistry 1】 (In formula (1), R 1 and R 2 each independently represents a hydrogen atom or an aliphatic hydrocarbon having 1 to 4 carbon atoms; m is 1 to 4, and n is 2 to 150.

2. 2. The antibacterial molded article according to claim 1, wherein the polycarbonate resin further contains a structural unit represented by the following formula (2): 【Chemistry 2】

3. 3. The antibacterial molded article according to claim 1, wherein the polycarbonate resin contains the structural unit represented by the formula (1) in an amount of 1% by weight or more and 80% by weight or less, based on 100% by weight of all structural units.

4. The antibacterial molded article according to any one of claims 1 to 3, wherein the polycarbonate resin has a specific viscosity of 0.15 or more and 1.5 or less.

5. The antibacterial molded article according to any one of claims 1 to 4, which has a water contact angle of 60° or less.

6. The antibacterial molded article according to any one of claims 1 to 5, wherein the constitutional unit represented by the formula (1) is a constitutional unit represented by the following formula (3): 【Chemistry 3】 (In formula (3), R 3 represents a hydrogen atom or a methyl group; n is a number from 2 to 150.

7. The antibacterial molded article according to any one of claims 1 to 6, which is an antibacterial molded article for use in housing equipment, refrigerators, home appliances, ATMs (automated teller machines), POS terminals, mobile phones, smartphones, personal computers, tablets, packaging materials, wallpaper, filters, switches, daily necessities and living materials, sanitary materials, clothing, and vehicles.

8. The antibacterial molded article according to any one of claims 1 to 7, wherein the member constituting the antibacterial molded article has a shape of a porous body, a fiber, a nonwoven fabric, a particle, a film, a sheet, a tube or a powder.

9. The antibacterial molded article according to any one of claims 1 to 8, wherein the coating has a film thickness of 0.1 µm to 1 mm.

10. The antibacterial molded article according to any one of claims 1 to 9, wherein the polycarbonate resin is coated by a painting method, a spraying method or a dipping method.

Citation Information

Patent Citations

  • Copolycarbonate

    JP2011241277A

  • Copolycarbonate

    JP2012201843A

  • Polyurethane and method for producing polyurethane

    JP2015189886A

  • Polycarbonate diol composition

    JP2019210314A

  • Sheet for cards and card

    WO2011145589A1